Hubungan antara Perceived Organizational Support dengan Readiness for Change pada Dokter Gigi di Bandung dan Cimahi: Kesiapan Dokter Gigi dalam Melakukan Pelayanan Kesehatan di Era Pandemi Covid-19 - Marlianti Hidayat; Stephanie Andamari; Gusriani Gusriani (Humanitas (Jurnal Psikologi), 2023)
Dentists are vulnerable to Covid-19 transmission when carrying out health services so that new health service procedures are established. The dentist's readiness for change becomes important to assist the implementation of new health procedures optimally and continuously. Perceived organizational support can enhance dentist’s readiness for change. Aim of this study was to determine the correlation between perceived organizational support (POS) and the dentist's readiness for change (RFC) in providing health services during the Covid-19 pandemic era. Pearson's Correlation was used in this study. The instrument used was rearranged based on the theory of POS (Eisenberger, 1986) and RFC (Holt, et al., 2007). There were 107 dentists from Bandung (86.9%) and Cimahi (13.1%) participated. Results showed that POS was significantly correlated to the dentist's RFC. POS is also significantly correlated with three aspects of RFC. Support from organizations can increase dentist’s RFC in providing health services in pandemic situation.